A problem-based approach to clinical education in dietetics. - Winter J; Matters H; Nowson C (Nutrition & Dietetics, 2002)
Developing the clinical skills and knowledge of dietetic students provides a challenge for both universities and health care agencies. Deakin University has recently adopted a group learning model using problem-based learning to deliver the clinical component of the Master of Nutrition and Dietetics course. This approach was designed to enhance integration of clinical theory and practice, develop closer links between on-campus and off-campus learning environments and provide students with more active learning experiences. The impact of the new approach was evaluated using student questionnaires, academic and competency outcomes, and a focus group convened with hospital supervisors. The evaluation indicated that students generally thought that this method of learning had helped to integrate their basic knowledge with dietetic case management. There was no difference in academic scores from the previous year and an apparent reduction in the number of students requiring additional placement time to meet competency standards. Hospital supervisors were supportive of the changes, although they had some reservations regarding the time and structure of clinical placements. As a result of this evaluation, recommendations for future development of the program include introducing problem-based learning to students earlier in their course, providing additional placement days during the block and increasing the amount of time dedicated to more complex topics. Based on the evaluation results obtained, this collaborative learning using a problem-based approach will continue to be used in the clinical education program at Deakin University. (Nutr Diet 2002;59:23-28)Key words: clinical education, problem-based learning, dietetics